(untitled) (Research, Society and Development, 2023)
Dance has numerous benefits for the development of being, mainly for child development. It provides a high quality of life, a more improved motor development, increased creativity and socialization, among others. The objective of this study will be to identify the importance of dance for child development. This is a field research, cross-sectional with a quantitative and descriptive nature. The study sample consisted of girls, practitioners and non-practitioners of dance, who live in the municipality of Arvorezinha-RS. Data were collected through the test: “Motor Development Proposal”, written by Gallahue, Ozmun and Goodway, where the groups were evaluated through specific test movements, and also through the Y Balance Test. It was possible to perceive that the motor development was presented in a more accurate way for the children who participated in the dance classes, in contrast to the children who only do the activities at school level.